The Development of West Java MSMEs as A Form of Economic Defense: An Analysis with Forecasting Methods - Hondor Saragih; Cut Maisyarah Karyati (Westscience Press, 2023)
The growth of Micro, Small, and Medium Enterprises (MSMEs) plays an increasingly vital role in driving local economies and supporting economic resilience in a region. This research aims to analyze and forecast the growth rate of MSMEs in the Bogor District, Sukabumi District, Garut District, Bandung District, and Cianjur District over the next 5 years using a forecasting method. Forecasting is an analytical approach that utilizes historical data to predict trends and patterns that may occur in the future. In the context of this study, historical data encompass various factors influencing MSME growth, such as the number of MSMEs, investments, government support, regulatory changes, as well as other external factors. This analysis employs various forecasting techniques, including statistical and machine learning methods, to generate accurate predictions. The outcomes of this research are expected to provide a deeper understanding of the key factors influencing MSME growth in these five districts and offer valuable insights for policymakers and stakeholders. Additionally, this research aims to make a significant contribution to the strategic planning of sustainable MSME development in the Bogor District, Sukabumi District, Garut District, Bandung District, and Cianjur District. With a better understanding of the dynamics of MSME growth, more effective steps can be identified to support local economic development.